LEADERSHIP EFFECTIVENESS AND EMPLOYEES’ JOB SATISFACTION IN SELECTED HOSPITALS IN DELTA STATE NIGERIA - ugo CHUKS okolie; Erakpotobo Oyovwevotu (Universitas Kuningan, 2023)
This study examines the impact of effective leadership on staff job satisfaction in a few hospitals in Delta State, Nigeria. Convenience sampling and a cross-sectional research design were used. For this study, a questionnaire was used as the research tool for data collection, and 107 respondents were deemed useful. The study's theoretical framework was the theory of transformational leadership. Correlation and linear regression analysis with the aid of Statistical Package for Social Sciences (SPSS) software version 23.0 were used to analysed the data that were gathered. The results of the study revealed that leadership effectiveness have positive significant influence on employees’ job satisfaction in selected hospitals in Delta State, Nigeria. The study's conclusion is that employees' perceptions of organisational culture and leadership styles have a significant impact on their perceptions of job satisfaction, which in turn affects their performance and behavior. The happiness of the workforce will be influenced by a leadership style that is in line with the requirements of the organisation. According to the study's findings, hospital management is advised, among other things, to take into account employees' abilities and to unlock their subordinates' potential by engaging in more transformational leadership behavior and cultivating a positive, less-political work environment that will increase their employees' job satisfaction.